An Economic Study of the Factors Affecting the Meat Chicken Production Farms in Bani Walid Municipality, Libya. - Lamah, Salah Alsunousi Lshteewi (Journal of Pure & Applied Sciences, 2021)
The study mainly aimed to identify  the most important factors affecting the meat chicken production farms in Bani Walid municipality. study relied on primary data collected from the meat chicken producers in the study sample in 2020. Adescriptive and quantitative economic analysis and farm productivity function models were used to meet the objectives of the study.  farm productivity to estimate economic efficiency. The field study indicated that the most important productive inputs affecting the production of meat chicken  were the number of chicks, the quantity of feed and the value of veterinary care, and the significant effect of these inputs was proven at the level of 5%. The results showed that the factor of total productivity elasticity was estimated at about 1.090, which reflects the relationship of increasing return to capacity. It also showed the results of the study that the coefficient of economic efficiency in the total productive capacity swallowed about 1.11,1.56,1.65 for each of the inputs mentioned study sample, respectively.